A Study on Angiographic profile of Acute Coronary Syndrome in Smokers (Academia Journal of Medicine, 2020)
Background: Coronary artery disease is a devastating disease precisely because an otherwise healthy person in the prime of life may die or become disabled without warning. The objectives of the study were to study the clinical profile, risk factors prevalence, angiographic distribution and severity of coronary artery stenosis in acute coronary syndrome (ACS) patients admitted in Cardiology Department of Cardiology Katuri Medical College & Hospital, Guntur. Subjects and Methods: A total of 208 patients of ACS were analyzed for various risk factors, angiographic patterns and severity of coronary artery disease in smokers vs non-smokers at Katuri Medical College, Andhra Pradesh. Results: Study group consisted of 208 subjects, of which 108(51.9%) subjects were smokers including all forms of tobacco use and 100 (48.1 Out of 108 study subjects in the smokers group, family history of CAD was present in 21 (19.4%) subjects. Killip class is not applicable to 13 (12%) study groups as they presented with Unstable Angina with ECG changes. Killip class 1 was most common presentation (67.6%) in smokers. 28 patients (25.9%) had LV dysfunction with EF < 50% by echocardiography. 80 patients (74.1%) had normal LV function. The mean EF was 55.56+/-10.16%. The median EF was 56.5%. LAD was type 3 in 100 (92.6%) patients and type 4 in 8 (7.4%) patients out of 108 study subjects. LAD type 3 was statistically significant with P value < 0.05 when compared with LAD type 4. No statistically significant difference was seen with respect to the Normal coronary arteries as CAG diagnosis between smokers and non-smokers (6.7% versus 8%, p>0.1, Not significant). Conclusion: Smokers were predominantly male and around 3 years younger than non-smokers. Diabetes mellitus and hypertension were less common among smokers and single-vessel disease was the more common angiographic finding for smokers as compared to 3-vessel disease for non-smokers. ST-segment elevation myocardial infarction in smokers despite younger age and the low atherosclerotic risk profile, in our region, emphasize the need for nicotine addiction management and smoking cessation campaigns at large and for pre-discharge counseling.
Keywords: Acute coronary syndrome; Left ventricles; ECG; Angiogram